Primo Leggero Napoletano. A Regimental History (1806-1815) - Adam Walczak (Nuova Antologia Militare)
This article concerns the history, organisation and service of the 1st Neapolitan Light Infantry Regiment (1º Reggimento d’Infanteria Leggera), a light infantry regiment in the service of the Napoleonic Kingdom of Naples (1806- 1815) during the Napoleonic Wars and its subsidiary conflicts. Formed at the beginning of Joseph Bonaparte’s reign by the newly emplaced French administration of Naples, the regiment’s formation came with the initiative of relegating costly counter-guerilla operations to local forces in the place of French regiments. With the advent of various conflicts across the Napoleonic empire – namely, popular revolts in Spain and the Tyrol – the regiment found itself sent as part of the Neapolitan military contingent to the Grande Armée. In the wider context of military operations, the regiment played no small part in the effective suppression of guerillas, growing to become one of the more capable regiments of the Neapolitan army. By the end of 1811, the regiment would find itself reformed within the Kingdom and would serve its final – and most glorious – campaign under the sceptre of Joachim Murat, being singlehandedly responsible for turning the Austrian flank at the Panaro in 1815. The regiment would be one of the few units that ended the 1815 campaign with its reputation enhanced.